2015
DOI: 10.1088/0004-637x/806/2/248
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF STELLAR MULTIPLICITY ON PLANET FORMATION. III. ADAPTIVE OPTICS IMAGING OFKEPLERSTARS WITH GAS GIANT PLANETS

Abstract: As hundreds of gas giant planets have been discovered, we study how these planets form and evolve in different stellar environments, specifically in multiple stellar systems. In such systems, stellar companions may have a profound influence on gas giant planet formation and evolution via several dynamical effects such as truncation and perturbation. We select 84 Kepler Objects of Interest (KOIs) with gas giant planet candidates. We obtain highangular resolution images using telescopes with adaptive optics (AO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 74 publications
7
102
0
Order By: Relevance
“…However, surveys of star-forming regions indicate that binaries with separations less than 50 au have significantly shorter disk lifetimes, while binaries with larger separations appear to have disk lifetimes comparable to those of single stars (e.g., Kraus et al 2012). In addition, Kraus et al (2016) surveyed 382 Kepler planet host stars and found that there is a s 4.6 deficit in stars with binaries closer than 50 au compared to field stars, suggesting that these close binaries negatively influence planet formation (see also Wang et al 2015). We therefore change our approach in this analysis to consider the multiplicity rate for companions interior and exterior to 50 au separately.…”
Section: Stellar Companion Fraction For Hot Jupiter Hosts Versus Fielmentioning
confidence: 99%
See 3 more Smart Citations
“…However, surveys of star-forming regions indicate that binaries with separations less than 50 au have significantly shorter disk lifetimes, while binaries with larger separations appear to have disk lifetimes comparable to those of single stars (e.g., Kraus et al 2012). In addition, Kraus et al (2016) surveyed 382 Kepler planet host stars and found that there is a s 4.6 deficit in stars with binaries closer than 50 au compared to field stars, suggesting that these close binaries negatively influence planet formation (see also Wang et al 2015). We therefore change our approach in this analysis to consider the multiplicity rate for companions interior and exterior to 50 au separately.…”
Section: Stellar Companion Fraction For Hot Jupiter Hosts Versus Fielmentioning
confidence: 99%
“…More recently, there have been four large direct imaging surveys for companions to transiting gas giant planet hosts (Wang et al 2015;Evans et al 2016). applied stellar density arguments to estimate that 12 out of their 49 targets have bound companions, while report candidate companions around 33 out of 74 systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bechter et al 2014;Wang et al 2014Wang et al , 2015. Photometric values for the Keplerband were computed by the method described in Brown et al (2011) using an arithmetic combination of gri colors.…”
Section: Aperture Photometrymentioning
confidence: 99%